Professional management competency for TVET teachers in engineering faculty at vocational college - Ismail, Khamsiah; Omar, Muhd Khaizer; Abdullah, Arnida (Human Resource Management Academic Research Society, 2019)
This study aims to explore the professional management of competencies among the TVET teachers in faculty of engineering at vocational college. Qualitative approaches were involved with case study and using a set of interview questions as a semi-structured interview guide for obtaining the data. A total of seven respondents from three vocational college in Selangor were involved in this study. Three respondent were selected from among the teachers, three respondents among the final year students who were on job training in industries and one of the director at vocational college. Instruments used in this study are questionnaires with semi structured, observations and documents analyzed. The data collected were analyzed using the N-vivo software application to answer the research questions related to this study. The results show that the components of competency needed were collaboration management, student management, workshop and classroom management, teaching preparation management, program and activity management and also documentation and reporting management